In Defense of Rationality: Mahmud Yunus’ Interpretation of The Qur’an on Religious Tolerance - MZ, Ahmad Murtaza; Aty Munshihah; M. Saiful Mujab; Nurul Aulia (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2024)
This article aims to explore the concept of religious tolerance according to Mahmud Yunus as presented in his work, Tafsir Qur’an Karim. This research is crucial for examining how Yunus rationalizes the concept of religious tolerance in his interpretation of Qur’anic verses. Mahmud Yunus’s interpretation in Tafsir Qur’an Karim is significance for understanding religious tolerance by integrating theological values with a rational approach, which is particularly relevant in a pluralistic society. Based on this premise, the article addresses two research questions: first, how does Mahmud Yunus interpret verses related to religious tolerance in Tafsir Qur’an Karim? Second, what form of rationality does Mahmud Yunus employ in his understanding of religious tolerance in Tafsir Qur’an Karim? This research employs a qualitative methodology, utilizing both primary and secondary sources. Content analysis is used to examine these sources. The findings of this study reveal that Mahmud Yunus considers religious tolerance to be integral part of Islamic teachings as explained in the Qur’an. Additionally, Yunus asserts that the practice of religious teachings by Muslims should be based on critical values and religious texts. Undoubtedly, Mahmud Yunus’s interpretation is influenced by his educational and socio-historical background, particularly the Islamic revival movement in Minangkabau.